Assessing Outcomes of Long-Term Research Collaboration - Creamer, Elizabeth G. (Canadian Journal of Higher Education, 2004)
This paper explores the link between research collaboration and innovation among faculty, as indicated by a self-reported assessment of the contribution of a co-authored publication to knowledge. Findings challenge the assumption that collaborators are rarely involved in theory development and the practice of crediting only the lead author for the intellectual content of a co- authored publication.